Peak oil and the Apocalypse: Apocalyptic imaginaries as a threat to politics proper - Pull,Emil (2014)
This thesis will examine the discourse of peak oil understood from a post-political perspective and challenge the un-reflexive assumption of peak oil as a natural challenger to current hegemony. It will do so by constructing a theoretical framework for ‘politics proper’ through which the peak oil discourse will be assessed. The conclusion is that while peak oil offer the potential of a serious rupture with the current regime; the discourse is also infused with apocalyptical imaginaries and populist maneuvers threatening to render such a rupture insignificant. The thesis warns against letting apolitical infusion obscure and hinder the illumination of proper political subjects and diverse alternatives to our current regime.
Keywords: democracy; apocalyptic imaginaries; populism; post politics; Peak oil